Comparative effectiveness of a second-line biologic in patients with ulcerative colitis: vedolizumab followed by an anti-TNF versus anti-TNF followed by vedolizumab. Issue 5 (7th January 2022) - Miller, Charles; Kwok, Hanson; Harrow, Paul; Vega, Roser; Seward, Edward; Mehta, Shameer; Rahman, Farooq; McCartney, Sara; Parisi, Ioanna; Lim, Samuel Hsiang; Sharma, Esha; Samaan, Mark A; et al.
Abstract : Background: Sequential drug treatment with biological agents in ulcerative colitis (UC) is becoming increasingly complex. There are few studies comparing head-to-head outcomes in second-line treatments. The study assesses whether using anti-tumour necrosis factor (anti-TNF)-α therapy following the α4β7 integrin blocker vedolizumab (VDZ) or VDZ after an anti-TNF has more favourable clinical outcomes in UC in a real-world outpatient setting. Methods: Patients with UC who were exposed to first-line anti-TNF (adalimumab or infliximab) or VDZ who subsequently switched to the alternate class between May 2013 and August 2020 were identified by reviewing patient databases at 10 hospitals. Data were collected retrospectively using patient records. Baseline demographics, disease activity indices, biochemical markers, endoscopic Mayo score, colectomy rates, treatment persistence and urgent hospital utilisation composite endpoint (UHUC) rates were examined over a 52-week period. Results: Second-line week 52 treatment persistence was higher in the VDZ group (71/81, 89%) versus the anti-TNF group (15/34, 44%; p=0.0001), as were week 52 colectomy-free survival (VDZ: 77/80, 96%, vs anti-TNF: 26/32, 81%; p=0.009), week 52 UHUC survival (VDZ: 68/84, 81%, vs anti-TNF: 20/34, 59%; p=0.002) and week 52 corticosteroid-free clinical remission (CFCR) rates (VDZ: 22/34, 65%, vs anti-TNF: 4/20, 20%; p=0.001). Conclusion: Compared with second-line anti TNF usage, the VDZ second-line cohort had significantly higher 52-week treatment persistence, UHUC survival, higher colectomy-free survival rates and higher week 52 CFCR. These data suggest that VDZ is an effective biologic in UC as a second-line therapy after anti-TNF exposure. It highlights the effect of biological order on clinically important outcomes.